Laparoscopic High Uterosacral Ligament Suspension vs. Laparoscopic Sacral Colpopexy for Pelvic Organ Prolapse: A Case-Control Study - Campagna, Giuseppe; Vacca, Lorenzo; Panico, Giovanni; Vizzielli, Giuseppe; Caramazza, Daniela; Zaccoletti, Riccardo; Marturano, Monia; Granese, Roberta; Arcieri, Martina; Cianci, Stefano; Scambia, Giovanni; Ercoli, Alfredo (Frontiers in Medicine, 2022)
Introduction: Laparoscopic sacral colpopexy is the gold standard technique for apical prolapse correction but it is a technically challenging procedure with rare but severe morbidity. Laparoscopic high uterosacral ligament suspension could be a valid technically easier alternative using native tissue. Material and methods: In the period from 2015 to 2018, 600 women were submitted to laparoscopic sacral colpopexy while 150 to laparoscopic high uterosacral ligament suspension in three Italian urogynecology referral centers. We enrolled women with apical prolapse stage ≥ 2 alone or multicompartment descensus. To reduce allocation bias, we performed a propensity matched analysis. Women undergoing laparoscopic high uterosacral ligament suspension surgery were matched 1:2 to women undergoing laparoscopic sacral colpopexy. The cumulative proportion of relapse-free women in time was analyzed by the Kaplan-Meier method. The primary objective of this multicenter case-control retrospective study was to compare the recurrence rate while the secondary objectives were to compare feasibility, safety and efficacy of laparoscopic sacral colpopexy and laparoscopic high uterosacral ligament suspension in surgical treatment of pelvic organ prolapse. Results: 309 women were enrolled (103 laparoscopic high uterosacral ligament suspension; 206 laparoscopic sacral colpopexy). Median operatory time was significantly shorter in the laparoscopic high uterosacral ligament suspension group (P=0.0001). No statistically significative difference was found in terms of estimated blood loss, admission time, intraoperative and major early post-operative complications, post-operative pelvic pain, dyspareunia and de novo stress urinary incontinence. Surgical approach was the only independent risk factor for prolapse recurrence (RR 6.013 [2.965 – 12.193], P=0.0001). The objective cure rate was higher in the laparoscopic sacral colpopexy group (93.7% vs 68%, 193/206 vs 70/103, P=0.0001) with a highly reduced risk of recurrence (RR 5.430 [1.660 – 17.765]). Median follow up was 22 months. Conclusion: Both techniques are safe, feasible and effective. Laparoscopic sacral colpopexy remains the best choice in treatment of multicompartment and advanced pelvic organ prolapse while laparoscopic high uterosacral ligament suspension could be appropriate for moderate and isolated apical prolapse when laparoscopic sacral colpopexy is not suitable for the patient or to prevent prolapse in women at high risk at the time of the hysterectomy.